Effect of steam and CO2 on ethane activation over Zn-ZSM-5. Issue 1 (5th December 2017) - Mehdad, Ali; Gould, Nicholas S.; Xu, Bingjun; Lobo, Raul F.
Abstract : Hydrolysis of Zn(ii ) sites in Zn-ZSM-5 suppresses ethane oligomerization and aromatization. Abstract : The impact of steam and CO2 on ethane activation over 5% (w/w) Zn-ZSM-5 catalysts was investigated. The main products in He, steam and CO2 were mixtures of ethene, methane, benzene and toluene. CO2 clearly increased the formation rate of ethene and CO, and steam increased the formation rate of ethene. In addition, the presence of CO2 decreased the formation rates of methane and aromatics by factors of ∼3 and 7, respectively. Hydrogen formed from ethane dehydrogenation reacted with CO2, via the reverse water gas shift reaction, to form CO and water. Under vacuum, FTIR spectra of adsorbed ethene on Zn-ZSM-5 showed stronger adsorption on zinc Lewis acid sites than on Brønsted acid sites. In the presence of steam, strong adsorption of ethene on the zinc Lewis acid sites ( ν CC at 1595 cm −1 ) splits the spectra into two absorption bands (at 1650 and 1568 cm −1 ), implying the hydrolysis of Zn(ii ) sites to form Brønsted acid sites and Zn(OH) + sites. Hydrolysis of Zn(ii ) sites suppresses oligomerization/aromatization reactions. The changes in selectivity are reversible and can be stopped by decreasing water vapor pressure. The results confirm that Zn(OH) + sites are effective in ethane dehydrogenation, but the Zn(ii ) sites are necessary for aromatization. The absence of aromatization reactions in the presence of steam shows that Zn(ii ) sites catalyze aromatization at faster rates than Brønsted acid sites.